2008
DOI: 10.1016/j.jacc.2008.01.066
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Differences Between Men and Women After Percutaneous Coronary Interventions

Abstract: The 30-day mortality after PCI in men and women has decreased in the past 25 years. After accounting for baseline risks, no differences in short-term or long-term mortality were observed between men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(65 citation statements)
references
References 30 publications
0
62
0
3
Order By: Relevance
“…13 For the present study, we included only patients from the Rochester area (Olmsted County) who had undergone PCI between January 1, 1994, and June 30, 2008, and and follow-up data were considered only for the earliest PCI. Because the Mayo Clinic is the only location in Olmsted County that performed PCI during the study period, the study sample very closely approximates a community-based sample of people undergoing PCI in Olmsted County.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 For the present study, we included only patients from the Rochester area (Olmsted County) who had undergone PCI between January 1, 1994, and June 30, 2008, and and follow-up data were considered only for the earliest PCI. Because the Mayo Clinic is the only location in Olmsted County that performed PCI during the study period, the study sample very closely approximates a community-based sample of people undergoing PCI in Olmsted County.…”
Section: Methodsmentioning
confidence: 99%
“…13 For the present study, we included only patients from the Rochester area (Olmsted County) who had undergone PCI between January 1, 1994, and June 30, 2008, and were discharged alive. If patients had Ͼ1 PCI, their CR and follow-up data were considered only for the earliest PCI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported stroke rates of 0.1-0.4% [1][2][3][4][5][6][7][8][9]. Catheterization-related acute stroke is associated with high in-hospital mortality and prevalence of overall major complications [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Moreover, for those women treated with PCI, unadjusted mortality ( Figure 2) and (vascular and bleeding) complication rates ( Figure 3) remain significantly higher than in men. 5,6 Whether these sex differences are explained by pathophysiology by impaired access to guideline-recommended therapies, by biology or bias, by lack of a robust evidence base in women, or by the artificial comparison between women and men as their control group, continues to be actively debated. Certainly, the seemingly paradoxical findings of a higher prevalence of risk factors, more severe angina symptoms but a similar (or lesser) extent of epicardial coronary disease, and of a higher prevalence of congestive heart failure despite better of left ventricular systolic function in women compared with men undergoing coronary revascularization, are likely based on underlying sex differences in vascular and myocardial physiology, structure, and function.…”
mentioning
confidence: 99%